Differentiating Stakeholder Theories - Kaler, John (Journal of business ethics, 2003)
Following on from work on stakeholder identification, this paper constructs a typology of stakeholder theories based on the extent to which serving the interests of non-shareholders relative to those of shareholders is accepted as a responsibility of companies. A typology based on the division of stakeholder theories into normative, descriptive, and instrumental is rejected on the grounds that the latter two designations refer to second order theories rather than divisions within stakeholder theory and the first is a designation which, for the purposes of business ethics, applies to all stakeholder theories. The crucial distinction between stockholder and stakeholder theory is argued to be their respective rejection and acceptance of role-specific responsibilities toward non-shareholders that are `ultimate objective fulfilling'. From this starting point, a typology is constructed using a division of stakeholder theories into those which do and do not give priority to the interests of shareholders over those of non-shareholders, do and do not posit perfect duties towards non-shareholders as well as shareholders, do and do not accept accountability to non-shareholders as well as shareholders.